FEATURES OF PROFESSIONAL AND PRACTICAL PHYSICAL TRAINING OF VOCATIONAL SCHOOL STUDENTS - Khasanov Akhadjon Tursinovich (Journals Park Publishing, 2025)
The article describes the specialized practical nature of professional and practical physical training conducted in vocational schools, associated with the field of labor and military activity, and proves the need for serious scientific development of a professional curriculum in this regard.
Keywords: Physical qualities, training, state standard, pedagogical testing, tool, method, exercise, professional activity.